An Efficient Model for Accurate Evaluation of Consumption Pattern in Distribution System Reconfiguration - Mahdavi, Meisam; Javadi, Mohammad Sadegh; Wang, Fei; Catalao, Joao P. S. P. S. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Consumption patterns of electric power systems are important for distribution companies, because of their significant impact on energy losses amount. Therefore, some incentives are suggested by distribution companies to energy consumers for correcting their consumption manner. For a specific load pattern, distribution system reconfiguration (DSR) is an effective way to mitigate energy losses. Hence, some research works have included load variations in the DSR problem to show the importance of consumption patterns in reconfiguration decisions. However, some of the specialized literature has ignored load changes in their reconfiguration models due to the high computational burden and processing time. On the other hand, the energy losses are calculated inaccurately if the consumption pattern is neglected. Consequently, the main goal of this paper is to investigate load pattern impact on switching sequences to find out how much is load profile important for minimization of energy losses in DSR The evaluations have been done for three well-known distribution systems using a classic optimization tool: A Mathematical Programming Language (AMPL).
Keywords: Consumption pattern; Costs; distribution network; efficient mathematical model; Energy loss; energy losses; Investment; Load management; Minimization; Power demand; reconfiguration; Voltage